Avaliação da dinâmica dos vetores de Leishmania sp. em fragmentos de Mata Atlântica e em meio ambiente urbano: influência dos fatores climáticos e ambientais e suas interferências na saúde pública - Silva, Francisco de Assis da (2018)
Leishmaniasis are parasitic diseases, caused by protozoa of the genus Leishmania spp. Currently, Leishmaniasis is a neglected diseases, with half a million new cases and approximately 60,000 deaths per year worldwide. It is a disease that disproportionately affects the most needy population and is transmitted by sand flies. The geographic distribution and prevalence of these vectors in Brazil has been the subject of some studies, however there is no information about the phlebotomine fauna. The objective of this study was to evaluate the prevalence and distribution of these sandflies in two types of environments, such as: Atlantic Forest fragments in Federal University of Paraíba, Campus I, João Pessoa/ PB, Brazil, besides neighborhoods such as: Castelo Branco, Bancários, São Rafael, Torre, Mangabeira and Miramar. In order to capture these sandflies, light traps (CDC) were used during 03 consecutive nights, as well as manual catches with a Castro vacuum traps, in the dry period (12 collections) and rainy (12 collections) between November 2016 and February 2017. During the study period, 222 sandflies were found. Of these, 143 (130 males and 13 females) in the Atlantic Forest environment of the UFPB and 79 in urban areas. During the dry period, in the 11 Mata fragments, three species of sandflies were captured: Lutzomya longipalpis, L. migonei and L. whitmani. In the rainy season, only the species L. longipalpis occurred, this species was the only one identified in the neighborhoods, both in the dry and rainy season. In this study it was evident that besides the climatic factors, environmental characteristics may also be involved in the distribution of these vectors.